AN ANALYSIS OF FIGURATIVE LANGUAGE IN TAYLOR SWIFT’S SONG LYRICS - Wilya Setiawati; Maryani Maryani (PROJECT (Professional Journal of English Education), 2018)
AbstractThis research is entitled An Analysis of Figurative Language in Taylor Swift's song lyrics it aims to know the types of figurative language that are used in Taylor swift lyrics and describe the contextual meaning of the figurative language used in Taylor's lyrics. The research data is obtained from two songs from one albumof Taylor Swift. The album titled Red with three songs taken entitles Red and 22. This research uses descriptive qualitative method in observation and library research in collecting data of this research. Figurative language found consists of simile, metaphor, hyperbole, paradox, irony and personification. In this research, these findingsshow that hyperbole is the most dominant in Taylor Swift’s song and based on the contextual meaning of overall song lyrics of Taylor Swift tell about conflict, pain heart and deeply treachery.Keywords: song, lyric, figurative language, contextual meaning